Nanoporous GeO2/Cu/Cu2O network synthesized by dealloying method for stable Li-ion storage. (20th March 2019) - Wang, Zhifeng; Zhang, Xiaomin; Yan, Yonghui; Zhang, Yongguang; Wang, Yichao; Qin, Chunling; Bakenov, Zhumabay
Abstract: Transition metal oxide Cu2 O anode is still not meeting the current market demands due to the low theoretical capacity and poor cycle stability. We herein report the synthesis of a nanoporous GeO2 /Cu/Cu2 O network by a straightforward dealloying method. The resulting material possesses high porosity which served to alleviate the stress incurred during lithiation/delithiation volume variation and presents good conductivity for fast electron transfer. Enhanced electrochemical performance is observed when measured as an anode material, delivering 715 mAh g −1 at 200 mA g −1 after 50 cycles and offered 504 mAh g −1 even at a high current density of 1600 mA g −1 after 150 cycles. Furthermore, the material also demonstrates excellent rate performance of 812, 782, 741, 695, 635 and 552 mAh g −1 at 100, 200, 500, 800, 1600 and 3200 mA g −1 current densities, respectively. The enhanced Li storage performances could be ascribed to the reticular ligament with high porosity, the increased conductivity by Cu as well as the improved capacity from GeO2 . Moreover, this work provides us a new material design strategy to fabricate various porous composite anodes with high capacity through a straightforward dealloying method in future for lithium-ion battery applications. Graphical abstract: Image 1 Highlights: Bimodal nanoporous GeO2 /Cu/Cu2 O network is fabricated by dealloying method. The bimodal porous material is designed by utilizing microstructural inheritance. The introduction of GeO2 improve the gross capacity of Cu2 O-based anode. Porous reticular ligament and conductive Cu agent guarantee the good properties.